A comprehensive overview of evolutionary relationships and geographic distributions of cownose rays: more valid taxa needing protective measures - Yasmim Trindade C. Cunha; Renata Daldin Leite; Lucas Gabriel Pereira da Silva; Vanessa Paes Cruz; Jorge Luiz S. Nunes; Matheus Marcos Rotundo; Paola Palacios-Barreto; Píndaro Diaz-Jaimes; Ana P. Barbosa Martins; M. Aaron Macneil; Chris G. Mull; José Augusto Pires Bitencourt; et al. (Reviews in Fish Biology and Fisheries, 2026)
Rays of the family Rhinopteridae Jordan & Evermann, 1896 are highly migratory and widely distributed in warm tropical and temperate waters. Along the Brazilian coast, the presence of two species has been recorded: Rhinoptera bonasus Mitchill, 1815 and Rhinoptera brasiliensis Müller, 1836. These stingrays are commonly caught as bycatch in trawl fisheries, however, the two species lack distinctive external morphological features that allow for reliable differentiation—species identification is primarily based on the shape and arrangement of teeth in the buccal plates. This study aimed to investigate the evolutionary history of the genus Rhinoptera and to explore which evolutionary drivers, such as biogeographic events or behavioral traits, have influenced its diversification. To achieve this, we analyzed both mitochondrial and nuclear genetic markers, focusing on the species occurring along the Brazilian coast. Specimens of both species were collected across various locations in Brazil, and additional sequences from other Rhinoptera species were obtained from GenBank. Our results reveal the presence of multiple cryptic species within Rhinoptera , particularly within R. bonasus , and likely in Rhinoptera steindachneri Evermann & Jenkins, 1891 and Rhinoptera javanica Müller & Henle, 1841. Notably, R. bonasus does not occur in Brazilian waters nor in parts of the Caribbean where a distinct cryptic sister lineage was identified. Based on our findings, we propose the resurrection of Rhinoptera lalandii Müller & Henle, 1841 as the species representing the lineage found along the Brazilian coast and the Eastern Atlantic Ocean. We suggest that philopatric behavior may represent one of several factors potentially influencing diversification within Rhinopteridae, although this hypothesis requires direct behavioral and population level validation. These findings highlight the urgent need for a comprehensive taxonomic revision of the family, as well as a reassessment of current conservation strategies to better reflect the hidden diversity within this group of species. Graphical abstract

Investigating the dynamics of the aquatic community in Oslofjord through time series analysis of eDNA - Sibusiso Mahlangu; Isabelle Ewers; Cintia Oliveira Carvalho; Audun Schrøder‐Nielsen; Micah Dunthorn; Hans Erik Karlsen; Grete Sørnes; Louise Chavarie; Dag Endresen; Jonathan Stuart Ready; Hugo J. de Boer; Quentin Mauvisseau (Journal of Fish Biology, 2025)
Understanding the temporal dynamics of marine communities is critical for assessing ecosystem health and guiding conservation efforts. Here, we conducted a survey using environmental DNA (eDNA) metabarcoding with two primer sets, MiFish and Elas02, to investigate seasonal and interannual changes in the fish community of Oslofjord (Norway) over two consecutive years. Using the MitoFish reference database through the Global Biodiversity Information Facility querying tool, we identified 63 fish species and found significant changes in the dominant taxa between seasons and years. Clupea harengus (Atlantic herring) consistently peaked in early spring, while Scomber scombrus (Atlantic mackerel) dominated winter months in the second year. The MiFish primer set showed increased species richness in the second year, whereas the Elas02 primer set showed stable richness despite compositional turnover. Non‐metric multidimensional scaling revealed distinct community separation between years in presence/absence of data, driven by species turnover rather than abundance read changes. Our findings support the use of eDNA metabarcoding to capture fine‐scale (bi‐monthly) temporal dynamics and emphasise the importance of multi‐year datasets for distinguishing ecological trends from stochastic changes. This strategy improves monitoring practices for marine ecosystems under anthropogenic stressors.

Dietary metabarcoding of keystone sardine species reveals the importance of their ichthyoplankton prey in food webs of the Southern Brazilian Bight fisheries - Anna Karolina Oliveira de Queiroz; Maria A. Gasalla; Marcele Laux; Renato Renison Moreira Oliveira; Fabricio dos Anjos Santa Rosa; Audun Schrøder‐Nielsen; Felippe A. Postuma; João Bráullio de Luna Sales; Hugo J. de Boer; Quentin Mauvisseau; Jonathan Stuart Ready (Fisheries Oceanography, 2024)
Clupeiform fishes are ecologically and economically important species contributing to industrial and artisanal fisheries worldwide. They represent key links in food webs, influencing the dynamic between trophic levels. The dietary interactions of these species are poorly studied in many regions, yet essential for fisheries management. To elucidate the role of these species in food webs of the Southern Brazilian Bight pelagic fisheries, we used metabarcoding analysis of fish stomach contents of Clupeiformes and possible predators. Onboard sampling from March to September 2016 allowed for processing of 87 stomach samples representing 31 species (including 12 samples representing three species of Clupeiformes). Links between trophic levels showed the predominance of Sardinella brasiliensis and Engraulis anchoita as important dietary items of a large range of fishes (28 species belonging to 18 families) and representing the majority of the total prey read abundance assigned to clupeiform fishes (~46% and ~32%, respectively). Opisthonema oglinum contributed to the diet of 16 species in 13 families and ~18% of total read abundance of clupeiform fishes as prey. The appearance of multiple clupeiform taxa in the diet of predators that are not commonly associated with pelagic prey indicates that ecosystem‐based fisheries management should not be separated between pelagic and demersal fisheries. The diet of Clupeiformes revealed an unexpectedly large diversity of fish species and a low proportion of invertebrates (

Traditional Knowledge Aids Description When Resolving the Taxonomic Status of Unsettled Species Using Classical and Molecular Taxonomy: The Case of the Shallow-Water Octopus Callistoctopus furvus (Gould, 1852) From the Western Atlantic Ocean - Manuella Dultra Jesus; João Bráullio de Luna Sales; Rodrigo Silvestre Martins; Jonathan Stuart Ready; Tarcisio Augusto S. Costa; Jonathan D. Ablett; Alexandre Schiavetti (Frontiers in Marine Science, 2021)
Shallow-water marine invertebrate fauna is diverse in tropical latitudes but generally poorly known. This is in part due the remoteness of many of these regions, and a lack of locally trained taxonomists. In such cases, the ethnoknowledge (i.e., information acquired from the sociocultural references of a given social group) of traditional human populations may be a valuable tool to elucidate gaps in the occurrence of some taxa. In this study, we used a combined approach of ethnoknowledge, classic taxonomy and molecular techniques to describe and diagnose an unsettled species of shallow-water octopus of the genus Callistoctopus . A neotype for the Brazilian eastern octopus Callistoctopus furvus ( Gould, 1852 ) is described along with some ecological notes. Octopuses were collected between April and May 2018 during field trips guided by artisanal octopus fishers of Bahia State (Brazil). A linear discriminant analysis showed that the morphology of C. furvus overlapped poorly with Callistoctopus sp. from the Caribbean and Macaronesia (Madeira Archipelago) as well as with Callistoctopus macropus stricto sensu from Mediterranean Sea. Analysis of mitochondrial large ribosomal subunit (rrnL, also known as 16S) gene and cytochrome C oxidase I (COI) showed that C. furvus differs genetically from European C. macropus and the other species in the genus. In general, C. furvus differs from other Atlantic/Mediterranean Callistoctopus species in having a slender body shape and longer mantle lengths. As in other species of the genus, C. furvus is nocturnal and inhabits sandy bottoms, seagrass beds and/or low-profile reefs. Interestingly, C. furvus burrows itself into the sand as a defense mechanism. In conclusion, we showed the support of ethnoknowledge for integrative biodiversity assessments in poorly surveyed remote areas in the western tropical Atlantic.

Enterococcus faecium as potential probiotic for ornamental neotropical cichlid fish, Pterophyllum scalare (Schultze, 1823) - Joel Artur Rodrigues Dias; Higo Andrade Abe; Natalino Costa Sousa; Raimundo Darley Figueredo Silva; Carlos Alberto Martins Cordeiro; Grazielle Fernanda Evangelista Gomes; Jonathan Stuart Ready; José Luiz Pedreira Mouriño; Maurício Laterça Martins; Paulo César Falanghe Carneiro; Alexandre Nízio Maria; Rodrigo Yudi Fujimoto (Aquaculture International, 2019)